Fiber to The Home (FTTH) Network Design with Addition of Optical Distribution Point (ODP) Using the Branching Method - Asril, Aprinal Adila; Maria, Popi; Lifwarda, -; Antonisfia, Yul; Hadi, Ronal (International Journal of Advanced Science Computing and Engineering, 2023)
Optical fiber is a transmission medium that uses light as a signal conductor. In order for optical fibers to be used and the benefits are felt, a network architecture is needed, namely FTTH. FTTH consists of active devices such as OLT and ONT as well as passive devices consisting of ODC, Closure, and ODP. In this design, it uses OLS as a light signal transmitter and produces input power. However, over time and the increase in population capacity and the number of access services available, of course, there are more and more requests for the installation of optical networks in customers' homes. Therefore, the most available FTTH device is ODP in order to be able to withdraw cables to customers' homes and continue to expand FTTH. Therefore, this study will discuss the addition of new ODP with the branching method. Using OPM as a measuring tool and calculating the power link budget to find out that the resulting attenuation value is no more than 28dB.